Outdoor Education in Times of the Pandemic – The Use of ActionBound Application - Nodzyńska-Moroń, Małgorzata; Bílek, Martin (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2022)
Education in times of the pandemic requires the use of new solutions. One of the biggest challenges is the implementation of out-of-body education. The article proposes a tool that allows the teacher to plan a trip (with various tasks and challenges). This application then allows the student to complete the task on their own, i.e. to go on a trip (with all the challenges planned by the teacher). The article describes the results of the study by 110 teachers who have been trained in the use of this application. The obtained results allow us to state that, regardless of gender, education and age, the vast majority of the surveyed teachers (50 to 75%) appreciate the role of the ActionBound application in the preparation of the trip and plan to use it in the near future.